Properties of Himalayan Nettle Fiber and Development of Nettle/Viscose Blended Apparel Textiles. Issue 1 (31st December 2023) - Samanta, Kartick K.; Roy, A. N.; Baite, H.; Debnath, S.; Ammayappan, L.; Nayak, L. K.; Singha, A.; Kundu, T. K.
ABSTRACT: Nettle plants are grown naturally as forest weeds in Himalayan region without much explored economic value. The plant remains under-explored as far as extraction of fiber for textile and other industrial applications are concerned. Present study highlights a complete information, starting from fiber extraction, retting, production of blended yarns & fabrics, coloration and products development along with cost analysis. Himalayan nettle plant was considered for fiber extraction through microbial retting, yielded 1.25% dry fiber. Extracted fiber was characterized in details for physical, mechanical, chemical, thermal and morphological properties. Fiber having fineness of 2.2–2.4 tex, tenacity of 10–16 cN/tex, and elongation of 3% was blended with viscose fiber in 100/0, 75/25, 50/50, and 25/75 ratios to produce blended yarns. Those yarns and bleached & dyed yarns were utilized as weft to produce fabric in handloom, keeping cotton yarn as warp. Yarns and fabrics properties were also evaluated in detail. Apparel textile products, like female fashion wear (cost $ 13) and "shawl" (cost $ 39), were produced. The developed products are not only be fashionable apparel but also be fully biodegradable. Research findings advocate that nettle plant may be considered as an untapped potential source for fiber extraction and application in apparel textile.